Modeling the Mixing of Components in a Rotary Kiln While Burning Municipal Waste to Ensure Rational Use of Energy - Krot O.P.; Rovenskyi O.I. (Problems of the Regional Energetics)
In Ukraine municipal waste is collected and delivered to a landfill. Municipal waste can be used as fuel to generate additional heat and electricity. The primary advantages of incineration are that waste volumes are reduced by an estimated, and the need for land and landfill space is greatly reduced. The plant has been designed by North–East Scientific Center using a thermocatalytic waste gas purification system with highly efficient dioxins reduction and heat energy recovery system. The technology of waste neutralization includes: a rotary kiln, an afterburner chamber, a new catalytic technologies for the treatment, a heat exchanger for heating combustion air, supply of alkali solution into the gas-escape channel, a carbon fiber adsorption filter. The organization of the right process of waste mixing in the rotary kiln allows increasing the efficiency of combustion, to equalize the combustion temperatures of the components of the waste and the completeness of the burning out of hazardous substances, which reduces the risk of their getting into the ash. The goal of the research is to build an analytical mathematical model of mixing of components in a rotary kiln. The model is based on the mathematical apparatus of Markov chains. The model allows to determine the concentration of the key component in any elementary volume of material circulating in the rotary kiln at any time and to calculate the statistical characteristics of the homogeneity of the mixture. The model will be used to research new designs of the equipment with rotary kilns.